2008
DOI: 10.1007/s00127-008-0337-x
|View full text |Cite
|
Sign up to set email alerts
|

Do needs, symptoms or disability of outpatients with schizophrenia influence family burden?

Abstract: Patients with schizophrenia with more needs cause greater family burden but not more subjective concerns in family members. The presence of patients' needs (daytime activities, alcohol and drug), severity of psychotic symptoms and disability are related to higher levels of family burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 33 publications
5
53
0
8
Order By: Relevance
“…This probably due to more complex illness and higher needs in those patients as compared to their counterparts not needing an extra care, therefore, explaining the higher burden and lower QOL in their caregivers (36). However, this observation may be due lack of effectiveness of the current day care program.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This probably due to more complex illness and higher needs in those patients as compared to their counterparts not needing an extra care, therefore, explaining the higher burden and lower QOL in their caregivers (36). However, this observation may be due lack of effectiveness of the current day care program.…”
Section: Discussionmentioning
confidence: 50%
“…Course of the illness, lack of social support and recent life events were the main factors found to be associated with a considerable impairment of caregivers' QOL in earlier studies (11,20,35,36). Severe positive symptoms of schizophrenia such as hallucination, delusion, aggressiveness and destructive behavior are known to cause distress to the caregivers and lower their QOL (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that schizophrenia afects 21 million people in the world [45]. Caregiving of a patient with schizophrenia involves assisting patients in daily tasks, which may disrupt caregiver behavior and their daily routine, among others [46]. Gupta et al [13] conducted a study to examine the health status of caregivers of patients with schizophrenia compared to noncaregivers and caregivers of adults with other conditions.…”
Section: Schizophreniamentioning
confidence: 99%
“…In both groups more than 40% of patients require more than 21 hours of care per week. This generates high levels of family burden as the carer dedicates many hours to the supervision or care of the ill person 9 and, in addition, the family burden levels are higher depending on the presence of symptoms and disability on the part of the patient [31][32][33] . The basic difference between the DiC and DeC groups is shown by the number of hours of health resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers have demonstrated that high levels of help from the caregivers are associated with a worse social functioning 9 , more symptoms (especially negative) 10,11 and more use of services 12 of the patients that they take care.…”
Section: Introductionmentioning
confidence: 99%